Designing a Rotary Composter Tool With an Ergonomic Approach to the Organic Garbage Processing Process - Fajar Aji Prasetiyo; Tri Budiyanto (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2020)
Garbage is one of the problems facing the Indonesian society. The production of garbage resulting from various individual activities is increasing each day. University of Ahmad Dahlan (UAD) Yogyakarta as one of the colleges in Yogyakarta has the potential to produce garbage of large amounts. Under the strategic plan of environmentally insightful campus development, garbage processing will be carried out by the institutions of University of Ahmad Dahlan and academic civitas. The average garbage produced by UAD 4 campus activities is 170 kg/day with an organic waste composition of 22.57 kg and non-organic 147.43 kg. During this time the garbage was directly distributed to the Piyungan landfill without being processed first, as the campus party had not been available garbage processing devices. The purpose of the study was to design organic garbage processing tools into compost fertilizers. The study used an ergonomic approach by utilizing anthropometric data in the determination of size from the design. Anthropometric data used in this study are Tinggi Bahu Duduk (TBD) or Shoulder High Sitting, Lebar Pinggul (LP) or Hip Width, Pantat Popliteal (PP) or Popliteal Butt, Tinggi Siku Berdiri (TSB) or Standing Elbow Height, Panjang Lengan Bawah (PLB) or Lower Arm Length, Lebar Bahu Atas (LBA) or Upper Shoulder Width, and Tinggi Lutut (TL) or Knee Height. The result of the study was an ergonomic Rotary Composter tool design operated by one person manually with dimensions 115 cm long, 148 cm wide, 115 cm tall, 60 cm barrel diameter, seat rest height 58.75 cm, 41.23 cm seat width, seat base length 45.39 cm, the distance between seats, tool height 114.94 cm, with tool 37.33 cm wide, seat rest 50 cm, 13 cm, seat width, and seat height 59.08 cm.